Complete genomic analysis of multidrug-resistance Pseudomonas aeruginosa Guangzhou-Pae617, the host of megaplasmid pBM413. (April 2018) - Liu, Junyan; Li, Lin; Peters, Brian M.; Li, Bing; Chen, Dingqiang; Xu, Zhenbo; Shirtliff, Mark E.
Abstract: Objectives: We previously described the novel qnrVC6 and bla IMP-45 carrying megaplasmid pBM413. This study aimed to investigate the complete genome of multidrug-resistance P. aeruginosa Guangzhou-Pae617, a clinical isolate from the sputum of a patient who was suffering from respiratory disease in Guangzhou, China. Methods: The genome was sequenced using Illumina Hiseq 2500 and PacBio RS II sequencers and assembled de novo using HGAP. The genome was automatically and manually annotated. Results: The genome of P. aeruginosa Guangzhou-Pae617 is 6, 430, 493 bp containing 5881 predicted genes with an average G + C content of 66.43%. The genome showed high similarity to two new sequenced P. aeruginosa strains isolated from New York, USA. From the whole genome sequence, we identified a type IV pilin, two large prophages, 15 antibiotic resistant genes, 5 genes involved in the "Infectious diseases" pathways, and 335 virulence factors. Conclusions: The antibiotic resistance and virulence factors in the genome of P. aeruginosa strain Guangzhou-Pae617 were identified by complete genomic analysis. It contributes to further study on antibiotic resistance mechanism and clinical control of P. aeruginosa . Highlights: The genome of multidrug-resistance P. aeruginosa Guangzhou-Pae617 has a length of 6, 430, 493 bp. The genome showed high similarity to two new sequenced P. aeruginosa strains isolated from New York, USA in 2012. With an average G + C content of 66.43%, 5881 predicted genes were identified. Five genes are involved in the "Infectious diseases" pathways. Two large prophages, 335 virulence factors including a type IV pilin, and 15 antibiotic resistance genes were identified.